Fenomena Ungkapan “Kardiman” sebagai Ekspresi Lingual dalam Kehidupan Sosial Masyarakat Madura: Kajian sosioliguistik - Haniah Haniah; Harsono Harsono (Universitas Madura, 2026)
This study examines the expression “Kardiman” as a linguistic phenomenon within Madurese society from a sociolinguistic perspective. The analysis focuses on its forms of use, social meanings, and the social factors that influence its emergence and development in everyday interaction. This research employs a descriptive qualitative approach. Data were collected through observation, in-depth interviews, and documentation of the expression’s usage across various social contexts. Data analysis was conducted using sociolinguistic theory, emphasizing the relationship between language, speakers, and social context. The findings reveal that the expression “Kardiman” has undergone semantic and functional expansion in Madurese communication practices. It is used as a medium for humor, satire, social labeling, emotional expression, and the representation of certain social behaviors. Its usage is influenced by age, social proximity, communicative context, and the influence of popular culture within the community.The study further indicates that the dynamics of “Kardiman” usage reflect the flexibility of language in responding to social change while maintaining local cultural identity in Madura. Language functions as a representation of continuously evolving social reality. This research contributes to sociolinguistic studies, particularly in understanding popular language phenomena in contemporary society and the interrelationship between language, culture, and social dynamics.